Active and Passive Smart Structures and Integrated Systems XVII 2023
DOI: 10.1117/12.2660857
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a dynamic active/passive noise cancellation of polyborosiloxane thin membrane gel

Abstract: This study proposes a multifunctional, thin membrane gel based on a formulation of PDMS and boron. The proposed gel offers a dynamic passive stimuli-responsive sound absorption at low frequencies, which can be transformed to active noise cancellation with the use of a secondary sound source. The passive behaviour of the proposed material is the result of a dynamic phase transition in the material’s polymeric network, activated by the interaction with the travelling sound pressure wave. The presence and extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In previous work 19 , we introduced these SSG based thin-membranes and managed to achieve high absorption coefficients (α > 0.9),in the low frequency range, which dynamically shifted to lower frequencies as the sound wave pressure wave was increased. In our following work we also demonstrated that this behaviour can be actively controlled, by the introduction of a secondary sound source, for applications where active noise control is required 20 . In this work, we demonstrate that the combination of thin membrane gels containing different amounts of B-O bonds can result in new high absorption peaks, not only due to the underlying mechanism of SSGs, but also due to the interaction between the membranes themselves, thus providing a highly tailorable solution for applications where noise cancellation at multiple frequencies is required.…”
Section: Introductionmentioning
confidence: 67%
“…In previous work 19 , we introduced these SSG based thin-membranes and managed to achieve high absorption coefficients (α > 0.9),in the low frequency range, which dynamically shifted to lower frequencies as the sound wave pressure wave was increased. In our following work we also demonstrated that this behaviour can be actively controlled, by the introduction of a secondary sound source, for applications where active noise control is required 20 . In this work, we demonstrate that the combination of thin membrane gels containing different amounts of B-O bonds can result in new high absorption peaks, not only due to the underlying mechanism of SSGs, but also due to the interaction between the membranes themselves, thus providing a highly tailorable solution for applications where noise cancellation at multiple frequencies is required.…”
Section: Introductionmentioning
confidence: 67%